Resilience in educational system: A systematic review and directions for future research. (May 2023) - Borazon, Elaine Quintana; Chuang, Hsueh-Hua
Abstract: This study proposes to map out the scientific production on resilience studies in the education context. This is in response to the clarion call for enhancing resilience in the education system as driven by recent disruptions and various environmental uncertainties. A total of 7230 search articles were extracted from Web of Science and Scopus, using the set criteria, covering the period 1980–2021. After screening for eligibility and duplications, 707 articles were analyzed. Among the literature reviewed through an inductive approach, research foci were categorized into five themes: culture and environment (15%), successful models and programs (18%), experiences and resiliency of learners (32%), characteristics of resilient students (19%), and teaching styles and resiliency of teachers (16%). These studies have highlighted the role of the environment, individual experiences and background, and educational institution's programs as enablers of resilience-building. This review contributes to the extant literature by proposing recommendations for research potentials toward building a more resilient educational system.